Evaluation of force released by deflection of orthodontic wires in conventional and self-ligating brackets - Rodrigo Hitoshi Higa; Nayara Thiago Semenara; José Fernando Castanha Henriques; Guilherme Janson; Renata Sathler; Thais Maria Freire Fernandes
ABSTRACT Introduction: The aim of the study was to evaluate deflection forces of rectangular orthodontic wires in conventional (MorelliTM), active (In-Ovation RTM) and passive (Damon 3MXTM) self-ligating brackets. Material and Methods: Two brands of stainless steel and nickel-titanium (NiTi) wires (MorelliTM and GACTM), in addition to OrmcoTM copper-nickel-titanium wires were used. Specimens were assembled in a clinical simulation device especially designed for this study and tested in an Instron universal testing machine. For the testing procedures, an acrylic structure representative of the maxillary right central incisor was lingually moved in activations of 0 to 1 mm, with readings of the force released by deflection in unloading of 0.5, 0.8 and 1 mm at a constant speed of 2 mm/min. Inter-bracket forces with stainless steel, NiTi and CuNiTi were individually compared by two-way ANOVA, followed by Tukey's tests. Results: Results showed that there were lower forces in conventional brackets, followed by active and passive self-ligating brackets. Within the brands, only for NiTi wires, the MorelliTM brand presented higher forces than GACTM wires. Conclusions: Bracket systems provide different degrees of deflection force, with self-ligating brackets showing the highest forces.